2010
DOI: 10.1007/s11250-010-9725-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pre-slaughter environment on some physiological parameters and meat quality in New Zealand rabbits (Oryctolagus cuniculus)

Abstract: The objective of this study was to examine the effect of pre-slaughter environment on physiology and meat quality in New Zealand rabbits. Pre-slaughter environment consisted of combined effects of social and non-social factors. For the experiment, 18 male New Zealand rabbits (Oryctolagus cuniculus), 3 months of age, were used. Some biochemical and meat quality parameters of the animals were measured, and the results were compared with the control group. The pre-slaughter environment significantly influenced so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…Intense artificial selection for growth rate of meat-type birds has resulted in a higher incidence of abnormal conditions (e.g., PSE-like meat), however this has not been found in rabbit meat ( Cavani et al ., 2009 ). Several researchers reported that the pre-slaughter environment (e.g., housing temperature, rearing techniques, feeding regimens, transport conditions and time) influenced blood biochemical parameters and meat traits in rabbits ( Combes et al ., 2010 ; Corino et al ., 2007 ; Sabuncuoglu et al ., 2011 ), thus producers should offer rabbits suitable pre-slaughter environmental conditions to obtain high-quality meat.…”
Section: Resultsmentioning
confidence: 99%
“…Intense artificial selection for growth rate of meat-type birds has resulted in a higher incidence of abnormal conditions (e.g., PSE-like meat), however this has not been found in rabbit meat ( Cavani et al ., 2009 ). Several researchers reported that the pre-slaughter environment (e.g., housing temperature, rearing techniques, feeding regimens, transport conditions and time) influenced blood biochemical parameters and meat traits in rabbits ( Combes et al ., 2010 ; Corino et al ., 2007 ; Sabuncuoglu et al ., 2011 ), thus producers should offer rabbits suitable pre-slaughter environmental conditions to obtain high-quality meat.…”
Section: Resultsmentioning
confidence: 99%
“…For this reason, compared to larger animals, rabbits may become stressed faster and more severely by food or water deprivation during transportation. Sabuncuoglu et al (2011) reported that the pre-slaughter environment is a potential stressor for rabbits. Due to socio-economic and cultural reasons, rabbit meat is still considered a niche product in Malaysia despite the steady increase in rabbit production.…”
Section: Resultsmentioning
confidence: 99%
“…Rabbits ( Oryctolagus cuniculus ) are bred in both tropic and subtropical regions of the world (Sabuncuoglu et al, 2011) and may be transported for a variety of reasons including breeding, use as pets, biomedical purposes, and slaughter. During transportation, rabbits may be exposed to various types of stressors including physical (such as high ambient temperature, vibration and changes in acceleration), psychological (such as confinement, noise and crowding during loading onto trucks, transport and marketing or at the abattoir prior to sticking) and physiological (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…During transport rabbits may be exposed to various stressors which can compromise both their welfare and meat quality. Several key factors have been identified, including deprivation of feed and water (Jolley, ; Verga et al., ), the loading method (Buil et al., ; Mazzone, Vignola, Giammarco, Manetta, & Lambertini, ; Verga et al., ), journey distance and duration (Lambertini, Vignola, Badiani, Zaghini, & Formigoni, ; Liste et al., , ; Maria et al., , ; Petracci, Bianchi, Biguzzi, & Cavani, ), stocking density (De la Fuente, Salazar, Ibanez, & de Chavarri, ), crate position on vehicle (Buil et al., ; Liste et al., , ), noise (De la Fuente, Diaz, Ibanez, & de Chavarri, ), social disruption and an unfamiliar environment (De la Fuente et al., ; Sabuncuoglu et al., ), lairage duration (Buil et al., ; Liste et al., ; Petracci et al., ; Verga et al., ), and environmental conditions (Buil et al., ; De la Fuente et al., , ; Liste et al., , ; Maria et al., , ; Petracci et al., ).…”
Section: Introductionmentioning
confidence: 99%